HUBUNGAN PAPARAN MEDIA INFORMASI DENGAN PENGETAHUAN PENYAKIT DEMAM BERDARAH DENGUE PADA IBU-IBU DI KELURAHAN SAMBIROTO SEMARANG - Adhiana Aysha Rohman; Syamsulhuda Syamsulhuda; Anung Sugihantono (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
Dengue has become a public health problem during the past 41 years in Indonesia. Incidence Rate of dengue fever in the city of Semarang from 2006 through 2014 is always much higher than Incidence Rate and the National Central Java. Sambiroto urban villages that are in the District of Tembalang IR DBD ranks third highest in Semarang with the number of cases up to April 2015 were 19 cases. The research objective is to analyze the relationship of media exposure information with the level of knowledge about dengue fever in the mother. This study uses a quantitative research with cross sectional approach. The study population was a mother with a number of 3691 and taken as many as 100 using incidental sampling method. Analyzed using univariate, bivariate, and multivariate analysis using test multilple Logistic Regression. The results showed that the respondents were knowledgeable good by 54%. Factors associated with exposure to media information is media exposure (p = 0.000), interpersonal media (p = 0.000), print media (p = 0.000), electronic media (p = 0.000). Analysis of data using multilple Logistic Regression test with 2 times the test and found that the electronic media is the most influential information medium of knowledge DBD.